POLITICAL PARTIES AND THE CHALENGE OF FREE AND FAIR ELECTIONS IN NIGERIA: A FOCUS ON KOGI STATE 2011 GUBERNATORIAL ELECTION - S. M. Omodia (European Scientific Journal, ESJ, 2012)
This research work unfolds party politics and the challenge of free and fair elections in Nigeria with specific focus on Kogi State 2011 gubernatorial election. The paper through the understanding of the typologies of political culture and political participation as frame work of analysis focuses on the concepts: political mobilization and education, party primaries and interparty contest as units of analysis for discussing the Nigerian electoral process. The paper thus argued that the low turnout of electorates during elections which was less than 50% of registered voters during the Kogi State gubernatorial election is an indication of the poor mobilization and educative function of political parties which poses a major challenge to free and fair elections. The paper further stated that, party primaries in the Nigerian state, especially in major political parties as manifested in Kogi State is often characterized by electoral manipulation and thereby adversely affecting aggregative function of political parties. This tends to have a far reaching implication on interparty contest as political environment in most cases is charged with divisiveness, party indiscipline, thuggery, ballot box snatching to mention a few. As a result, the paper recommend an enduring mobilization and education process by political parties which is anchored on the grassroots as means of acquiring support for the political system. This is coupled with the need to restructure political parties to be integrative of the people by encompassing people of like minds rather than been viewed as platforms for political contest.